Role of oral Iron therapy in anemic and non anemic pregnant women - T.Padmaja1 , Srinivas Ch2 , Bhagya Lakshmi K3 (Perspectives In Medical Research, 2017)
Introduction : Anemia is a common medical disorder affecting a lot of women in pregnancy in the developing countries. The occurrence of anaemia in pregnant women is attributed mainly to malnutrition. Anaemia might become fatal as to contribute to maternal mortality & morbidity. Hence present study is under taken to know the role of oral therapy in both anaemic & non anaemic pregnant women. Materials & Methods: The study was conducted at antenatal OPD between October 2005 to July 2006.Ninety pregnant women were selected & divided into 2 groups.44 normal pregnant women (control group) were compared with 46 pregnant women with anaemia(study group) aged between 20-30 years. Haematological parameters were analysed by SYSMEX auto analyser. In current study we compared haematological responses to oral iron therapy(Zincofer) in both control & study groups. Student ‘t’ test was used for comparison between study and control groups. Results: The change in RBC count between the two groups was insignificant over the pregnancy period. A significant increase in Hb%,MCH & MCHC has been observed in anaemic pregnant women over the trimesters with oral iron therapy which is an indicative of increased iron absorption . Conclusion: The study will be indicative about the rational use of iron in iron deficiency anemia. Daily oral iron supplementation is strongly recommended during pregnancy to reduce the prevalence of anemia